Characterization of vegetation fraction estimated using spot-vegetation NDVI data for regional climate modeling in India (MAUSAM, 2006)
lkj & ,e- ,e- 5 tSls eslksLdsy tyok;q fun’kksZa }kjk ouLifr ¼oh- ,Q-½ dh lwpuk nsus dk dk;Z egRoiw.kZ gSA fun’kZu ¼ekWMfyax½ esa lkekU; :Ik ls lcls vf/kd iz;qDr dh xbZ tyok;q laca/kh ekfld oh- ,Q-  gSA oh- ,Q- dh lwpuk,¡ ,u- vks- ,- ,- & ,- oh- ,p- vkj- vkj-  ,u- Mh- oh- vkbZ- HkweaMyh; vk¡dM+k lsVksa dk mi;ksx djrs gq, xqVesu vkSj bXukVkso ¼1988½ ¼th- vkbZ-½ }kjk rS;kj dh xbZ gSA bl 'kks/k&i= esa Hkkjrh; {ks= ds vizSy 1998 ls uoacj 2003 dh vof/k ds LikWV& ost+hVs’ku 10 fnolh; fefJr ,u- Mh- oh- vkbZ- ds mRiknksa dk mi;ksx djrs gq, 1 fd- eh- ds oh- ,Q- ds vk¡dM+k lsV rS;kj djus ds ckjs esa crk;k x;k gSA LikWV&osthVs’ku ds 0 % vkSj 100 % dh  oh- ,Q- ls laca) ,u- Mh- oh- vkbZ- dh laosnd fof’k"V izHkkolhek,¡ th- vkbZ- ds 0-04 vkSj 0-52 dh rqyuk esa Øe’k: 0-04 vkSj 0-804 ikbZ xbZaA th- vkbZ- ds tyok;q laca/kh oh- ,Q ds lkFk izkIr fd, x, oh- ,Q ds vk¡dM+ksa dh rqyuk dh xbZ gSA rhu v{kka’kh; {ks=ksa ¼ 24½ ds fy, oh- ,Q- ds fo’ys"k.k ls th- vkbZ- ls 15 % rd dh fHkUurkvksa dk irk pyk gSA o"kkZ&vk/kkfjr Ñf"k okys {ks= esa mYys[kuh; fHkUurk dk irk pyk gSA oh- ,Q- ls izkIr fd, x, ekSleh vkSj o"kZ&izfro"kZ dh fHkUurkvksa ds ifj.kkeksa ij fopkj&foe’kZ fd;k x;k  gSA Vegetation fraction (VF) is an important input in mesoscale climate models, such as MM5. The most commonly used VF inputs in modeling is the climatic monthly VF generated by Gutman and Ignatov (1998)  (GI) using NOAA-AVHRR NDVI global data sets. This paper reports the generation of 1 km VF data set using SPOT-VEGETATION 10-day composite NDVI products from April 1998 to November 2003 for the Indian region. Sensor-specific thresholds of NDVI associated with 0% and 100% VF for SPOT-VEGETATION were found to be 0.04 and 0.804, respectively, in contrast to 0.04 and 0.52 of GI. Comparison of derived VF with climatic VF of GI was carried out.  Analysis of VF for three latitudinal zones (24) indicated the differences up to 15 percent from GI.  Significant difference was observed for the area having rain-fed agriculture. Results of the seasonal and year-to-year variations of derived VF are discussed.